Odpowiedzi

2009-11-25T16:10:14+01:00
5a + 7 = 4b - 2
5b + 3 = 5a + 3b

5a = 4b - 9
a = ⁴/₅b - ⁹/₅

5b + 3 = 5(⁴/₅b - ⁹/₅) + 3b
2b = 4b - 9 -3
-2b = -12
b = 6

a= 0,8 × 6 - 1,8 = 3
2009-11-25T16:57:05+01:00
Mam nadzieje ze dobrze odczytalam
mamy uklad
5a + 7 = 4b - 2
5b + 3 = 5a + 3b

5a -4b =- 9
-5a+2b=-3
--------------------
-2b=-12
b=6

5a= -9+4b
b=6

5a=-9+24
b=6

a=3
b=6


zatem jeden bok to 5a+7 czyli 22
drugi bok to 5b+3 czyli 33
2009-11-25T17:08:19+01:00
5a + 7 = 4b - 2
5b + 3 = 5a + 3b

5a = 4b - 9
a = ⁴/₅b - ⁹/₅

5b + 3 = 5(⁴/₅b - ⁹/₅) + 3b
2b = 4b - 9 -3
-2b = -12
b = 6

a= 0,8 × 6 - 1,8 = 3